The class and the classroom are unbeatable scenarios to mobilize the knowledge - Arreaza Beberide, Fernando (Avances en Supervisión Educativa, 2009)
The article has two parts. In the first one, it is described the teaching-centered approach that has been traditionally used to transmit knowledge. This approach corresponds to the separate subject curriculum that is based on the concept of knowledge organized by isolated disciplines and that has remained stable since the nineteenth century. In the second part, as an alternative, it is described an approach geared to the development of key competences.
Keywords: knowledge; teaching approaches; transversal and specific key competentes; lesson unit; assessment units; homogenous and heterogeneous classes